PERILAKU MASYARAKAT DAN PERANSERTA PEMERINTAH DAERAH DALAM PENGELOLAAN SAMPAH DI KOTA TEMBILAHAN - Achmad Mulyadi; Sofyan Husein; Zulfan Saam (Program Pascasarjana Universitas Riau, 2009)
This research is conducted with the aim to find out people's attitudes in waste managementwhere waste management has not implemented with a maximum in accordance with UU No. 18Tahun 2008 on Household Waste Management, Household and Similar Specific as a basis forhousehold waste management has not done with maximum, especially in urban communities oneof them in Tembilahan City and knowing participation of local government waste managementin Tembilahan city and find relationship or influence people's behavior and participation oflocal government waste management in Tembilahan City. Social behavior in waste managementin Tembilahan city is still at the level of new homeland was highly influenced by the level ofpublic education is still low 54% below high school and 56% self-employed job anddissemination of information is not maximized. Participation of local government in wastemanagement in Tembilahan city is still very low homeland where the provision of which is stillnot fit the needs, socialization is still lacking, data collection and monitoring have not done.Community empowerment by the government has not at all to walk, so the role of the localgovernment is still not optimally. In order for waste management in the Tembilahan City bebetter to do some things that do socialization, socialization is expected with this community cantake advantage of available facilities, and provision of facilities as needed, separation of wetand dry waste and distribution facility or facilities evenly, providing a tool transportmotorcycles or wagon to improve service access to public housing. Further research is also inorder to find an appropriate method of waste management in accordance with the geographicalconditions of city waste and homeland.